Microsurgical Techniques and Postoperative Outcomes After Total and Subtotal Nasal Reconstruction: A Systematic Review. Issue 6 (6th June 2022) - Gasteratos, Konstantinos; Spyropoulou, Georgia-Alexandra; Chaiyasate, Kongkrit; Siotos, Charalampos; Vlachopoulos, Nikolaos; Friedstat, Jonathan
Abstract : Background: Multiple microsurgical techniques for nasal reconstruction have been described in the literature. Given the gaps in the literature regarding evidence-based reviews for total and subtotal nasal reconstruction using microsurgical techniques, the purpose of this study was to provide a thorough presentation of the most popular microvascular techniques and their outcomes (functional and aesthetic) for total or subtotal nasal defects. Methods: A systematic search was performed using PubMed, Google Scholar, and Cochrane Library on free flap techniques for restoration of nasectomy defects. The keywords were "nasal reconstruction, " "nose, " "nasectomy, " "rhinectomy, " and "microvascular." Inclusion criteria for analysis in the study were the largest clinical case series published in English within the past 15 years with more than 8 patients. Studies were analyzed for patient demographics, etiology of nasal loss, surgical approaches to reconstruction, outcomes, and complications. The current study was registered at the International Prospective Register of Systematic Reviews and conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Results: The initial search yielded 302 results. Eleven articles with a total of 232 patients met the inclusion criteria. The radial (n = 85) and ulnar forearm flaps (n = 20), auricular helical rim (n = 87), and anterolateral thigh flap (n = 30) were the most commonly reported free flaps in nasal reconstruction. The main etiologic factors were malignancy and trauma. The most common complication was partial flap necrosis. Conclusions: The auricular helical and radial forearm flaps represent the most used free flaps for total and/or subtotal nasal defects with satisfactory patient outcomes.